Sex-Specific Association between Childhood BMI Trajectories and Asthma Phenotypes - Danny Wadden; Leigh-Anne Allwood Newhook; Laurie Twells; Jamie Farrell; Zhiwei Gao (International Journal of Pediatrics)
Background. Asthma and obesity are two common health problems in the pediatric population. Obesity is associated with several comorbidities which are of great consequence. Excess adipose tissue has been linked to asthma in a number of studies. However, little is known about childhood body mass index (BMI) trajectories and the development of asthma phenotypes. Objective. The current study aims to investigate the significance of BMI trajectories over childhood and the risk of asthma phenotypes. Methods. The current study is a prospective cohort of children aged 0-2 years who were followed every two years for eight years through cycles one to five in the National Longitudinal Survey of Children and Youths (NLSCY). Statistical analysis: a latent class growth modelling (LCGM) method was used to identify BMI trajectory patterns from cycles one to five. Multiple imputation (number of imputations=5) was carried out to impute children with missing values on height or weight information. Sampling weights and 1,000 bootstrap weights were used in SAS PROC SURVEYLOGISTIC to examine the association between BMI trajectory and asthma phenotypes (persistent or transient asthma) in a multivariate analysis. Results. The study consisted of 571,790 males and 549,230 females. Among them, 46% of children showed an increasing trajectory in terms of change in BMI percentile during childhood, followed by the stable-trajectory group (41%) and decreasing-trajectory group (13%). After controlling for confounding factors, females in the increasing BMI trajectory group were four times more likely to be associated with persistent asthma (OR = 4.09; 95% CI:1.04-16.15; p = 0.0442) than females in the stable BMI trajectory group. No such relationship was found in males. The BMI trajectory was not significantly associated with risk of transient asthma for either sex. Conclusion. We report a female-specific association between increasing adiposity, measured by BMI, and persistent asthma.